Real-Time Microwave Moisture Measurement Of Nickel Ore In Conveyor Applications - Win Adiyansyah, Indra; Nurulhalim, Hassim (Penerbit UTM Press, 2016)
There are many advantages of knowing the moisture content of material in a real-time basis. Moisture content is a crucial parameter that affects material handling. Various technologies have been introduced but only a few were successfully applied for on-line moisture measurement in bulk mineral applications. This paper describes a Random Stratified Sampling Sweeping Microwave technique, moisture content measurement technique that reduce interference, annulling or superimposing signal, which are common errors in moisture measurement using microwave transmission technology. The technique is used for nickel ore running on a belt conveyor exiting the rotary dryer. The experimental results showed regression of 0.85, standard error of 0.18, and accuracy of 0.7wt%.